Madrasah Head's Strategy in Improving the Culture of Educational Quality Based on Madrasah-Based Management at MTsN 5 Tangerang - Wahyu Fajar Nugraha; Armai Arief; Herwina Bahar (Asian Social Work Journal, 2023)
This study aims to find strategies for madrasah heads to improve quality culture based on madrasah-based management. This research was conducted at MTSN 5 Tangerang located in Tangerang Regency, Banten Province. Research methods used in this study use qualitative methods with a phenomenological study approach. Data collection techniques are carried out through interviews, documentation, and observation. This study involved several participants, such as madrasah heads, teachers, education staff, students, and madrasah committees. The results of this study try to confirm the compatibility between the phenomena that occur in MTSN 5 Tangerang with management theories such as G.R.Terry's theory, Beck and Cowan's theory, McKinsey's 7S Framework theory, and Deming's theory. According to the findings of the researchers, the strategy of the head of the MTSN 5 Tangerang madrasah in improving the culture of education quality is carried out through planning, organizing, directing, and supervising based on madrasah-based management principles that are independence, achievement, environmental insight, and moral character. The characteristics of madrasah-based management are indicators of the success of the madrasah head's strategy in improving the culture of education quality. The implications of the strategy of the head of the MTSN 5 Tangerang madrasah in improving the culture of education quality can be seen from the increase in educational inputs, processes, and outputs in achieving the National Education Standards (SNP). Based on the description above, this dissertation research is considered important considering that the head of the madrasah has a central role in making strategic policies in the madrasah. The researcher's suggestion is that this research is expected to be a reference model for the government, public and private madrassas, and heads of madrassas in realizing quality and equitable Islamic education.